2013
DOI: 10.1128/aem.00703-13
|View full text |Cite
|
Sign up to set email alerts
|

Linked Expressions of nap and nos Genes in a Bradyrhizobium japonicum Mutant with Increased N 2 O Reductase Activity

Abstract: To understand the mechanisms underlying the increased N 2 O reductase activity in the Bradyrhizobium japonicum 5M09 mutant from enrichment culture under N 2 O respiration, we analyzed the expression of genes encoding denitrification reductases and regulators. Our results suggest a common regulation of nap (encoding periplasmic nitrate reductase) and nos (encoding N 2 O reductase). N itrous oxide (N 2 O) is a key greenhouse gas that also damages the ozone layer. Soybean nodules emit N 2 O under field conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
(28 reference statements)
0
10
0
1
Order By: Relevance
“…The induction of napE expression depended on the nasT product since β‐galactosidase activity in the nasST mutant was not significantly different from that in USDA110 (Table ). The β‐galactosidase activities by the P nirK ‐ lacZ and P norC ‐ lacZ fusions in the nasS and nasST mutants did not differ significantly from that in USDA110 (Table ), in line with the absence of nirK and nor induction in 5M09 reported earlier (Sánchez et al ., ). This suggests that the regulation of transcription of denitrification genes by NasST is specific to the nos and nap genes, and occurs under aerobic and anaerobic conditions.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The induction of napE expression depended on the nasT product since β‐galactosidase activity in the nasST mutant was not significantly different from that in USDA110 (Table ). The β‐galactosidase activities by the P nirK ‐ lacZ and P norC ‐ lacZ fusions in the nasS and nasST mutants did not differ significantly from that in USDA110 (Table ), in line with the absence of nirK and nor induction in 5M09 reported earlier (Sánchez et al ., ). This suggests that the regulation of transcription of denitrification genes by NasST is specific to the nos and nap genes, and occurs under aerobic and anaerobic conditions.…”
Section: Resultsmentioning
confidence: 97%
“…Inoculation of soybeans with the Nos ++ strain 5M09 mitigated N 2 O emission in both pot and field experiments (Itakura et al ., ). We have also shown that in strain 5M09, transcription of nosZ , nosR and nosD (genes from the N 2 O reduction cluster), and napA (encoding the catalytic subunit of the periplasmic nitrate reductase), was higher than in USDA110 (Sánchez et al ., ). The induced transcription of nos and nap genes did not depend on the FixLJ‐FixK 2 ‐NnrR and RegSR‐NifA regulatory cascades (Sánchez et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The calculated production of typical and atypical nosZ transcripts in all other relevant microbial species we identified based on the sequencing of typical and atypical nosZ transcripts was not significantly affected by biochar addition. Recent studies revealed that well-studied strains of some of these species ( Ensifer meliloti 1021 and Bradyrhizobium diazoefficiens USDA 110) are able to grow with externally supplied N 2 O as sole electron acceptor 68, 69 . Thus, these strains take up N 2 O from the environment and further reduce it to N 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Denitrification can be considered as a modular process and each nitrogen oxide reductase appears to provide a selectable benefit independent of other denitrification enzymes (Graf et al ., ; Roco et al ., ). In this respect, B. diazoefficiens is able to grow with N 2 O as the sole electron acceptor (Sánchez et al ., ). In this bacterium, the nosRZDFYLX cluster encodes Nos (NosZ) and several ancillary proteins required for its expression, maturation and maintenance.…”
Section: Introductionmentioning
confidence: 97%